EVALUASI KELENGKAPAN PENULISAN RESEP PASIEN DI INSTALASI FARMASI RSKJ SOEPRAPTO PROVINSI BENGKULU SEBELUM DAN SESUDAH AKREDITASI - Versita, Riana; Ikhsan, Ikhsan; Kristiani, Maria Herliana Esa (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
A prescription is a written request from a doctor or dentist to a pharmacist, either in paper or electronic form to provide and deliver drugs to patients in accordance with applicable regulations. Good prescription should contain enough information that allows a pharmacist concerned to understand what medication will be administered to patients. Writing and filling prescription clearly needs to be considered to avoid medication error. This research aimed the completeness of prescription at pharmaceutical installation RSKJ Soeprapto Bengkulu in 2019 based on administrative and pharmaceutical aspects. Samples on this study were taken with the Quota Sampling technique using Slovin formula with error rate of 5%. The results showed that the administartif completeness description before accreditation is 73,25% and after accreditation is 81.21%, while the description of aspects of pharmaceutical completeness before accreditation is 91.05% and after accreditation is 99% From 4444 samples studied in 2017 and 2019 there was an increase in completeness in writing prescriptions both in the administrative aspect, namely 7,96% and 7,95% from the pharmaceutical aspect